Sektor Basis di Kabupaten Blitar, Jawa Timur: Analisis PDRB Kabupaten Blitar Tahun 2010-2016 - KRISTIAN BUDITIAWAN (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2019)
There is a striking inequality between the northern region and the southern region of East Java. The northern region has an infrastructure that is able to lift economy up. Unlike the northern region, the southern region of East Java does not have adequate infrastructure so that the economy development tends to be slower. The reason is mostly caused by the geographical conditions of the region, especially the Kab. Blitar, which is hilly and rocky, barren and arid. This study aims to find out the base sector, to know the business fields that have competitiveness, and to know the structure of the economy in Blitar Regency 2010-2016 period. The analysis technique used is Location Quotient Analysis (LQ), Dynamic Location Quotient (DLQ) Analysis, and classic Shift-Share Analysis. The results of this study are the base sectors in Blitar Regency covering agriculture, forestry and fisheries; information and communication; real estate; government administration, defense and compulsory social security; education services; and health services and social activities. Business fields that have competitiveness are agriculture, forestry and fisheries; mining and excavation; wholesale and retail trade, car and motorcycle repair; and financial and insurance services. And the economic structure of Blitar Regency in the period 2010-2016 is supported by four business fields, there are agriculture, forestry and fisheries; wholesale and retail trade, car and motorcycle repair; processing industry; and construction. Keyword: base sector, competitiveness, LQ, DLQ, Shift-Share